Scarring Effect Pandemi Covid-19 Pekerja Lulusan Pendidikan Tinggi Berdasarkan Lapangan Usaha - Idris, M. Umar (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
Employee with tertiary education graduate in Indonesia have also been affected by the socio-economic impacts of Covid-19, but there has been little specific discussion from scarring effect perspective. This research aims to analyze the decline in income among employees with tertiary education graduates during the Covid-19 pandemic, by using Sakernas (National Labor Force Survey) data of August 2021 and descriptive and inferential Multinomial Logistic Regression methods. This research concludes that the scarring effect, in the form of income reduction, is more pronounced among tertiary-education graduates worker in the service sector and industrial sectors. In terms of job type, the income decline is more pronounced among blue-collar and gray-collar workers. In contrast, white-collar workers, who constitute the majority of higher-education graduates worker, experienced relatively less scarry in terms of income decline. After controlling the dependent and independent variable with individual characteristics, the research found that industrial sector variable significantly influences the income decline among educated workers, followed by those in the service sector, and the lowest in agricultural sector. As the regression results, university-educated workers in the industrial sector are likely to experience a 2.468 times greater of income decline compared to those working in the agricultural sector and compared to those with stable incomes. Meanwhile, educated workers in service sector are likely to experience a 1.454 times greater of income decline compared to those working in agricultural sector and compared to those with stable incomes.